Ptaquiloside biotoxin in ferns of the genus Pteridium - Rodríguez-Salazar, Massiel (2022)
Introduction. The ferns of the genus Pteridium are characterized by their wide habitat and adaptive power that allows their establishment in various types of soils and altitudes. They have the ability to produce a toxin called ptaquiloside. Objective. To gather a current body of updated knowledge on the ptaquiloside toxin present in ferns of the genus Pteridium. Development. The ferns of the genus Pteridium produce ptaquiloside biotoxin, especially in young phenological stages and in the fronds. The hydrolysis of this toxin at the biological level generates compounds with cytotoxic and genotoxic properties. Ptaquiloside can produce enzootic bovine hematuria, be deposited in the milk of the animal that consumes it and affects the health of dairy consumers. The biotoxin has an immunosuppressive effect in cattle, which can favor the papilloma virus, and also causes blindness in sheep. It is associated with esophageal and gastric cancer in humans living in areas populated by ferns of the genus Pteridium. The carcinogenic effect of ptaquiloside is generated because it causes DNA alkylation at N3 adenine or N7 guanine, 24 h after ingestion. For the eradication of ferns in pastures, mechanical control, biological control, and chemical control, are the most important. Conclusion. The biotoxin ptaquiloside represents a risk to human and animal health, which can spread to soil, water bodies, and food. More research is needed to take measures to reduce its effects.